A Simple Solver for the Two-Fluid Plasma Model Based on PseudoSpectral Time-Domain Algorithm (Communications in Computational Physics, 2021)
We present a solver of 3D two-fluid plasma model for the simulation ofshort-pulse laser interactions with plasma. This solver resolves the equations of thetwo-fluid plasma model with ideal gas closure. We also include the Bhatnagar-Gross-Krook collision model. Our solver is based on PseudoSpectral Time-Domain (PSTD)method to solve Maxwell's curl equations. We use a Strang splitting to integrate Eulerequations with source term: while Euler equations are solved with a composite schememixing Lax-Friedrichs and Lax-Wendroff schemes, the source term is integrated witha fourth-order Runge-Kutta scheme. This two-fluid plasma model solver is simple toimplement because it only relies on finite difference schemes and Fast Fourier Transforms. It does not require spatially staggered grids. The solver was tested againstseveral well-known problems of plasma physics. Numerical simulations gave resultsin excellent agreement with analytical solutions or with previous results from the literature.
Keywords: Two-fluid plasma model; 3D Hydrodynamic code; Lax-Wendroff; composite scheme; PSTD; laser-plasma interaction.